Potential Impact of Local Anesthetics Inducing Granulocyte Arrest and Altering Immune Functions on Perioperative Outcome - Kolle G (Dove Medical Press, 2021)
Gesche Kolle,1,* Thomas Metterlein,1,2,* Michael Gruber,1 Timo Seyfried,1 Walter Petermichl,1 Sophie-Marie Pfaehler,1 Diane Bitzinger,1 Sigrid Wittmann,1 Andre Bredthauer1 1Department of Anesthesiology, University Medical Centre Regensburg, Regensburg 93053, Germany; 2Department of Anesthesiology, Klinikum Ansbach, Ansbach 91522, Germany*These authors contributed equally to this workCorrespondence: Andre BredthauerDepartment of Anesthesiology, University Medical Centre Regensburg, Franz-Josef-Strauss-Allee 11, Regensburg 93053, GermanyTel +49 941/944-7801Fax +49 941/944-7802Email andre.bredthauer@ukr.deIntroduction: Local anesthetics (LAs) are frequently used during anesthesia; however, they may influence granulocyte function which in turn could modify immune responses in the perioperative period. Therefore, the aim of this study was to investigate the impact of clinically used doses of bupivacaine and lidocaine on granulocyte function with regard to migration, reactive oxygen species (ROS) production, neutrophil extracellular traps (NETosis) formation, and viability.Methods: A total of 38 granulocyte-enriched samples from healthy subjects were obtained by whole blood lysis. Polymorphonuclear neutrophil (PMN) samples were incubated simultaneously with different concentrations of either bupivacaine (0.03– 3.16 mmol/L) or lidocaine (0.007– 14.21 mmol/L), or without drug (control). Live cell imaging was conducted in order to observe granulocyte chemotaxis, migration, ROS production, and NETosis. Flow cytometry was used to analyze viability and antigen expression.Results: The track length (TL) of PMNs exposed to bupivacaine concentrations of 0.16 mmol/L and above significantly decreased compared to the control. Low concentrations of lidocaine were associated with slight but significant increases in TL, whereas this changed with concentrations above 1.4 mmol/L, showing a significant decrease in TL. PMN incubated with bupivacaine concentrations of 1.58 mmol/L and above or lidocaine concentrations of at least 3.6 mmol/L showed no migration or chemotaxis at all. Time to onset of maximal ROS production and time for half-maximal NETosis decreased in a dose-dependent manner for both substances. Equipotency in NETosis induction was reached by bupivacaine (1.1 mmol/L) at significantly lower concentrations than lidocaine (7.96 mmol/L). Cell viability and oxidative burst were unaffected by LAs.Conclusion: Local anesthetics in clinically used doses ameliorate granulocyte defense mechanisms, thus indicating their potentially decisive effect during the perioperative period.Keywords: local anesthetics, granulocytes, immune modulation, surgical trauma, inflammation